Aerobic photooxidative synthesis of 2-aryl-4-quinazolinones from aromatic aldehydes and aminobenzamide using catalytic amounts of molecular iodine1. Issue 78 (26th August 2015) - Nagasawa, Y.; Matsusaki, Y.; Nobuta, T.; Tada, N.; Miura, T.; Itoh, A.
<x xml:space="preserve">Abstract</x> This study reports a safe, mild, and environmentally benign synthetic method toward 2-aryl-4-quinazolinones through a cyclization–oxidation sequence using a catalytic amount of iodine, harmless visible light irradiation, and molecular oxygen.